Development of a mobile application for dental diagnosis - Wong, Keith Zi Hao (Nanyang Technological University, 2021)
Oral health is important to us as it concerns our teeth. Just like how we visit doctors when we are not feeling well in any part of our bodies, we need to visit the dentist regarding any issues with our oral health. This project aims to create an application in which it allows users to have a preliminary diagnosis of one‟s oral health at any point of time, to help people overcome dentophobia so as to allow them to have an ease of mind before visiting the dentist, and allows the users to look for dental clinics around them which they can make an appointment without much of a hassle. This project also aims to allow kids to have an interactive and fun time while learning about oral hygiene using the various methods and quizzes. Besides targeting dental patients, this application also allows the various dental clinics to manage dental appointments of patients. In this project, the maps, appointment, quiz and tips functions are built on React Native and Google Firebase Services.